Trivalent chromium passivator for high-corrosion-resistance zinc-nickel electroplated coating and preparation method of trivalent chromium passivator
By introducing nanotitanium dioxide reinforced particles modified by sodium hydroxide and silane coupling agent into the trivalent chromium passivator, and a composite synergist of cetyl trimethyl ammonium bromide and sodium dodecyl benzene sulfonate, the problem of insufficient anti-corrosion of the existing trivalent chromium passivator was solved, and a high corrosion resistance trivalent chromium passivator was prepared, which significantly improved the corrosion resistance of the zinc-nickel electroplating layer.
Patent Information
- Application Number
- CN202510092204.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
AI Technical Summary
The existing trivalent chromium passivating agents still lack corrosion resistance to zinc-nickel electroplating in complex environments, making it difficult to meet the environmental protection needs of high humidity air and corrosive gases.
By sequentially performing surface hydroxylation of sodium hydroxide and surface amino-modified nanotitanium dioxide with silane coupling agent KH-550 as reinforced particles, and with cetyl trimethylammonium bromide and sodium dodecylbenzenesulfonate as compound synergist, physically blending with trivalent chromium salt, organic acid, nitric acid, oxidant and deionized water, a highly corrosion-resistant trivalent chromium passivator was prepared.
The trivalent chromium passivator forms an excellent passivation film on the surface of the zinc-nickel electroplating layer, which significantly improves corrosion resistance, can effectively delay corrosion in complex environments, and improves the corrosion resistance of the electroplating layer.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of trivalent chromium passivators, and specifically relates to a trivalent chromium passivator for a high corrosion-resistant zinc-nickel electroplating layer and a preparation method thereof. Background Art
[0002] Although the zinc-nickel electroplating layer itself has a certain anti-corrosion ability, its corrosion resistance is still very limited in a complex environmental system, such as high humidity air, the presence of corrosive gases, etc., and it is very easy to rust. Based on this, many existing technologies will use passivators to passivate the surface of the zinc-nickel electroplating layer to form a passivation film to further improve the corrosion resistance. However, these passivators still have certain disadvantages that limit their actual application effect. This is because most of these passivators are chromium-free passivators or trivalent chromium passivators. Chromium-free passivators do not contain chromium elements and have the advantages of environmental protection and greenness. However, their cost is relatively expensive and high, and they are difficult to use on a large scale. Compared with hexavalent chromium passivators, trivalent chromium passivators are less toxic and are ideal substitutes for hexavalent chromium passivators. However, although people have been optimizing the formula of trivalent chromium passivators, their corrosion resistance has been criticized and there is still a lot of room for improvement. Summary of the invention
[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer and a preparation method thereof. The present invention creatively uses nano titanium dioxide which is sequentially surface hydroxylated by sodium hydroxide and surface amino-modified by a silane coupling agent KH-550 as reinforcing particles, and uses hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate as compound synergists, so that the two are physically mixed with a trivalent chromium salt, an organic acid, nitric acid, an oxidant and deionized water to prepare a trivalent chromium passivator, which is very suitable for surface passivation of zinc-nickel electroplating layers and has excellent corrosion resistance.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer is prepared from trivalent chromium salt, organic acid, nitric acid, oxidant, reinforcing particles, a composite synergist and deionized water.
[0006] As a preferred technical solution of the present invention, the mass ratio of the trivalent chromium salt, the organic acid, the nitric acid, the oxidant, the reinforcing particles, the composite synergist and the deionized water is 30-40:25:2-3:5-10:3-4:1:900-950.
[0007] As a preferred technical solution of the present invention, the trivalent chromium salt is chromium nitrate.
[0008] As a preferred technical solution of the present invention, the organic acid includes oxalic acid and malonic acid; the mass ratio of the oxalic acid to the malonic acid is 1:0.5-1.
[0009] As a preferred technical solution of the present invention, the oxidant includes sodium nitrate and cobalt nitrate; the mass ratio of the sodium nitrate to the cobalt nitrate is 1:1.
[0010] As a preferred technical solution of the present invention, the enhanced particles are prepared by the following steps:
[0011] Step A: Mix sodium hydroxide solution and nano titanium dioxide at a mass ratio of 100-150:2-3 at room temperature with stirring for 1-2h, then hydrothermally react at 110-130°C, naturally cool to room temperature, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80°C until constant weight, to obtain component A;
[0012] Step B: Mix ethanol, component A, silane coupling agent KH-550 and deionized water in a mass ratio of 100-150:2-3:0.1-0.2:1 under ultrasonic stirring at 40-70° C. for 6-10 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, and the preparation is completed.
[0013] Furthermore, the mass fraction of the sodium hydroxide solution in step A is 15-20%.
[0014] Furthermore, the hydrothermal reaction time in step A is 24-26 hours.
[0015] Furthermore, the power of the ultrasound in step B is 300-500W.
[0016] As a preferred technical solution of the present invention, the compound synergist comprises hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate; the molar ratio of the hexadecyltrimethylammonium bromide to the sodium dodecylbenzenesulfonate is 1:0.4-0.5.
[0017] A method for preparing a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, the preparation method comprising the following steps:
[0018] Add trivalent chromium salt to deionized water, then stir and mix at 40-50°C for 10-15 minutes, then add organic acid, stir and mix for 1-2 hours, add oxidant, reinforcing particles and compound synergist, stir and mix for 30-45 minutes, cool naturally to room temperature, and finally add nitric acid, stir and mix for 10-15 minutes to complete the preparation.
[0019] A method for using a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, the method comprising the following steps:
[0020] Completely immerse the zinc-nickel electroplating layer in a trivalent chromium passivating agent at 30-40°C for 60 seconds, take it out, wash it with deionized water, and finally heat treat it at 70-80°C for 15-20 minutes, and naturally cool it to room temperature.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention creatively uses nano-titanium dioxide that has been surface-hydroxylated with sodium hydroxide and surface-amino-modified with a silane coupling agent KH-550 as reinforcing particles, and uses hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate as compound synergists, so that the two are physically mixed with a trivalent chromium salt, an organic acid, nitric acid, an oxidant and deionized water to prepare a trivalent chromium passivator, which is very suitable for use in the surface passivation of zinc-nickel electroplating layers and has excellent corrosion resistance.
[0023] (2) The present invention creatively uses nano-titanium dioxide which has been surface hydroxylated by sodium hydroxide and surface amino-modified by silane coupling agent KH-550 as reinforcing particles, and uses hexadecyltrimethylammonium bromide and sodium dodecylbenzene sulfonate as compound synergists, so that after the two are introduced into the trivalent chromium passivator, the trivalent chromium passivator can be endowed with a more excellent passivation ability, and the passivation effect on the zinc-nickel electroplating layer is good, and the corrosion resistance is excellent. On the one hand, the nano-titanium dioxide itself can be filled in the passivation film by virtue of the small size effect, and play a role of sealing and physical barrier, thereby improving the compactness. At the same time, after the hydroxylation treatment, it can rely on a stronger interaction force to adhere to the surface of the zinc-nickel electroplating layer, thereby achieving better interface bonding. The amino modification can participate in the passivation cross-linking system, generate a passivation film with a more complex structure, reduce film defects to a certain extent, and delay the migration rate of the corrosive medium. On the other hand, the synergistic compounding of hexadecyltrimethylammonium bromide and sodium dodecylbenzene sulfonate can form a more stable dispersion system, promote the uniform distribution of passivation sites, and further improve the corrosion resistance. DETAILED DESCRIPTION
[0024] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0025] The nano titanium dioxide in all the embodiments and comparative examples of the present invention was purchased from Ningbo Jiwei Nano New Material Technology Co., Ltd. The product name is rutile nano TiO2 powder and the model is JWN-TO-R15.
[0026] Example 1
[0027] A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer is prepared from trivalent chromium salt, organic acid, nitric acid, oxidant, reinforcing particles, a composite synergist and deionized water.
[0028] The mass ratio of the trivalent chromium salt, the organic acid, the nitric acid, the oxidant, the reinforcing particles, the composite synergist and the deionized water is 30:25:2:5:3:1:900.
[0029] The trivalent chromium salt is chromium nitrate.
[0030] The organic acid includes oxalic acid and malonic acid; the mass ratio of the oxalic acid to the malonic acid is 1:0.5.
[0031] The oxidant includes sodium nitrate and cobalt nitrate; the mass ratio of the sodium nitrate to the cobalt nitrate is 1:1.
[0032] The enhanced particles are prepared by the following steps:
[0033] Step A: Mix sodium hydroxide solution and nano titanium dioxide at a mass ratio of 100:2 at room temperature for 1 hour, then perform a hydrothermal reaction at 110° C., cool naturally to room temperature, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60° C. until constant weight, to obtain component A;
[0034] Step B: ethanol, component A, silane coupling agent KH-550 and deionized water are mixed in a mass ratio of 100:2:0.1:1 at 40°C under ultrasonic stirring for 6 hours, filtered, the filter residue is taken, washed with deionized water, and finally vacuum dried at 60°C until constant weight, and the preparation is completed.
[0035] The mass fraction of the sodium hydroxide solution in step A is 15%.
[0036] The hydrothermal reaction time in step A is 24 hours.
[0037] The power of the ultrasound in step B is 300W.
[0038] The compound synergist comprises hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate; the molar ratio of the hexadecyltrimethylammonium bromide to the sodium dodecylbenzenesulfonate is 1:0.4.
[0039] A method for preparing a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, the preparation method comprising the following steps:
[0040] Add trivalent chromium salt to deionized water, then stir and mix at 40°C for 10 minutes, then add organic acid, stir and mix for 1 hour, add oxidant, reinforcing particles and compound synergist, stir and mix for 30 minutes, cool naturally to room temperature, and finally add nitric acid, stir and mix for 10 minutes to complete the preparation.
[0041] Example 2
[0042] A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer is prepared from trivalent chromium salt, organic acid, nitric acid, oxidant, reinforcing particles, a composite synergist and deionized water.
[0043] The mass ratio of the trivalent chromium salt, the organic acid, the nitric acid, the oxidant, the reinforcing particles, the composite synergist and the deionized water is 40:25:3:10:4:1:950.
[0044] The trivalent chromium salt is chromium nitrate.
[0045] The organic acid includes oxalic acid and malonic acid; the mass ratio of the oxalic acid to the malonic acid is 1:1.
[0046] The oxidant includes sodium nitrate and cobalt nitrate; the mass ratio of the sodium nitrate to the cobalt nitrate is 1:1.
[0047] The enhanced particles are prepared by the following steps:
[0048] Step A: Mix sodium hydroxide solution and nano titanium dioxide at a mass ratio of 150:3 at room temperature for 2 hours, then perform a hydrothermal reaction at 130° C., cool naturally to room temperature, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 80° C. until constant weight, to obtain component A;
[0049] Step B: ethanol, component A, silane coupling agent KH-550 and deionized water are mixed in a mass ratio of 150:3:0.2:1 at 70° C. under ultrasonic stirring for 10 h, filtered, the filter residue is taken, washed with deionized water, and finally vacuum dried at 80° C. until constant weight, and the preparation is completed.
[0050] The mass fraction of the sodium hydroxide solution in step A is 20%.
[0051] The hydrothermal reaction time in step A is 26 hours.
[0052] The power of the ultrasound in step B is 500W.
[0053] The compound synergist comprises hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate; the molar ratio of the hexadecyltrimethylammonium bromide to the sodium dodecylbenzenesulfonate is 1:0.5.
[0054] A method for preparing a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, the preparation method comprising the following steps:
[0055] Add trivalent chromium salt to deionized water, then stir and mix at 50°C for 15 minutes, then add organic acid and stir and mix for 2 hours, add oxidant, reinforcing particles and compound synergist and stir and mix for 45 minutes, cool naturally to room temperature, and finally add nitric acid and stir and mix for 15 minutes to complete the preparation.
[0056] Example 3
[0057] A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer is prepared from trivalent chromium salt, organic acid, nitric acid, oxidant, reinforcing particles, a composite synergist and deionized water.
[0058] The mass ratio of the trivalent chromium salt, the organic acid, the nitric acid, the oxidant, the reinforcing particles, the composite synergist and the deionized water is 35:25:2.5:8:3.5:1:930.
[0059] The trivalent chromium salt is chromium nitrate.
[0060] The organic acid includes oxalic acid and malonic acid; the mass ratio of the oxalic acid to the malonic acid is 1:0.7.
[0061] The oxidant includes sodium nitrate and cobalt nitrate; the mass ratio of the sodium nitrate to the cobalt nitrate is 1:1.
[0062] The enhanced particles are prepared by the following steps:
[0063] Step A: Mix sodium hydroxide solution and nano titanium dioxide at a mass ratio of 130:2.5 at room temperature for 1.5 hours, then perform a hydrothermal reaction at 120° C., cool naturally to room temperature, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 70° C. until constant weight, to obtain component A;
[0064] Step B: ethanol, component A, silane coupling agent KH-550 and deionized water are mixed in a mass ratio of 130:2.5:0.15:1 at 60° C. under ultrasonic stirring for 8 h, filtered, the filter residue is taken, washed with deionized water, and finally vacuum dried at 70° C. until constant weight, and the preparation is completed.
[0065] The mass fraction of the sodium hydroxide solution in step A is 18%.
[0066] The hydrothermal reaction time in step A is 25 h.
[0067] The power of the ultrasound in step B is 400W.
[0068] The compound synergist comprises hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate; the molar ratio of the hexadecyltrimethylammonium bromide to the sodium dodecylbenzenesulfonate is 1:0.45.
[0069] A method for preparing a trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, the preparation method comprising the following steps:
[0070] Add trivalent chromium salt to deionized water, then stir and mix at 45°C for 13 minutes, then add organic acid, stir and mix for 1.5 hours, add oxidant, reinforcing particles and compound synergist, stir and mix for 40 minutes, cool naturally to room temperature, and finally add nitric acid, stir and mix for 13 minutes to complete the preparation.
[0071] Comparative Example 1
[0072] Based on Example 3, the silane coupling agent KH-550 in step B was replaced by an equal weight of deionized water, and the rest remained unchanged.
[0073] Comparative Example 2
[0074] Based on Example 3, the sodium hydroxide solution in step A was replaced with an equal weight of deionized water, and the rest remained unchanged.
[0075] Comparative Example 3
[0076] On the basis of Example 3, the reinforcing particles were changed to nano-titanium dioxide of equal weight, and the rest remained unchanged.
[0077] Comparative Example 4
[0078] On the basis of Example 3, no reinforcing particles are added during the preparation of the trivalent chromium passivator, and the rest remain unchanged.
[0079] Comparative Example 5
[0080] Based on Example 3, hexadecyltrimethylammonium bromide was replaced by an equal weight of sodium dodecylbenzenesulfonate, and the rest remained unchanged.
[0081] Comparative Example 6
[0082] On the basis of Example 3, sodium dodecylbenzenesulfonate was replaced by an equal weight of hexadecyltrimethylammonium bromide, and the rest remained unchanged.
[0083] Comparative Example 7
[0084] On the basis of Example 3, no composite synergist is added during the preparation of the trivalent chromium passivator, and the rest remain unchanged.
[0085] Test Example 1
[0086] Passivation effect test:
[0087] The zinc-nickel electroplating layer was passivated using the trivalent chromium passivator prepared in Example 3 and Comparative Examples 1-7, respectively (the zinc-nickel electroplating layer was completely immersed in a trivalent chromium passivator at 35° C. for 60 seconds, taken out, washed with deionized water, and finally heat treated at 75° C. for 20 minutes, and naturally cooled to room temperature, wherein the thickness of the zinc-nickel electroplating layer was 0.1 mm and the nickel content was 8 wt %), thereby obtaining various different samples, and then the samples were subjected to a neutral salt spray test with reference to the standard GB / T 10125-1997, and it was observed whether white rust was generated on the samples after the test cycle reached 1000 hours.
[0088] Table 1. Passivation effect test results
[0089] Whether white rust occurs Example 3 no Comparative Example 1 yes Comparative Example 2 yes Comparative Example 3 yes Comparative Example 4 yes Comparative Example 5 yes Comparative Example 6 yes Comparative Example 7 yes
[0090] Comparison between Example 3 and Comparative Examples 1-7 shows that:
[0091] The difference between Comparative Example 1 and Example 3 is that the enhanced particles are not modified with amino groups.
[0092] The difference between Comparative Example 2 and Example 3 is that the reinforcing particles are not hydroxylated.
[0093] The difference between Comparative Example 3 and Example 3 is that the reinforcing particles are replaced by nano-titanium dioxide of equal weight.
[0094] The difference between Comparative Example 4 and Example 3 is that no reinforcing particles are introduced into the trivalent chromium passivating agent.
[0095] The difference between Comparative Example 5 and Example 3 is that hexadecyltrimethylammonium bromide is replaced by an equal weight of sodium dodecylbenzenesulfonate.
[0096] The difference between Comparative Example 6 and Example 3 is that sodium dodecylbenzenesulfonate is replaced by an equal weight of hexadecyltrimethylammonium bromide.
[0097] The difference between Comparative Example 7 and Example 3 is that the trivalent chromium passivator does not introduce a compound synergist.
[0098] From the comparison between Test Example 1, Example 3 and Comparative Examples 1-7, it can be seen that the trivalent chromium passivator prepared by the present invention is very suitable for surface passivation of zinc-nickel electroplating layers and has excellent corrosion resistance.
[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer, characterized in that: The trivalent chromium passivator is prepared from trivalent chromium salt, organic acid, nitric acid, oxidant, reinforcing particles, compound synergist and deionized water.
2. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The mass ratio of the trivalent chromium salt, the organic acid, the nitric acid, the oxidant, the reinforcing particles, the composite synergist and the deionized water is 30-40:25:2-3:5-10:3-4:1:900-950.
3. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The trivalent chromium salt is chromium nitrate.
4. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The organic acid comprises oxalic acid and malonic acid; the mass ratio of the oxalic acid to the malonic acid is 1:0.5-1.
5. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The oxidant includes sodium nitrate and cobalt nitrate; the mass ratio of the sodium nitrate to the cobalt nitrate is 1:
1.
6. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The enhanced particles are prepared by the following steps: Step A: Mix sodium hydroxide solution and nano titanium dioxide at a mass ratio of 100-150:2-3 at room temperature with stirring for 1-2h, then hydrothermally react at 110-130°C, naturally cool to room temperature, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80°C until constant weight, to obtain component A; Step B: Mix ethanol, component A, silane coupling agent KH-550 and deionized water in a mass ratio of 100-150:2-3:0.1-0.2:1 under ultrasonic stirring at 40-70° C. for 6-10 hours, filter, take the filter residue, wash with deionized water, and finally vacuum dry at 60-80° C. until constant weight, and the preparation is completed.
7. A trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 6, characterized in that: The mass fraction of the sodium hydroxide solution in step A is 15-20%.
8. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 6, characterized in that: The hydrothermal reaction time in step A is 24-26 hours.
9. The trivalent chromium passivator for a highly corrosion-resistant zinc-nickel electroplating layer according to claim 1, characterized in that: The compound synergist comprises hexadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate; the molar ratio of the hexadecyltrimethylammonium bromide to the sodium dodecylbenzenesulfonate is 1:0.4-0.
5.
10. A method for preparing a trivalent chromium passivating agent for a highly corrosion-resistant zinc-nickel electroplating layer according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Add trivalent chromium salt to deionized water, then stir and mix at 40-50°C for 10-15 minutes, then add organic acid, stir and mix for 1-2 hours, add oxidant, reinforcing particles and compound synergist, stir and mix for 30-45 minutes, cool naturally to room temperature, and finally add nitric acid, stir and mix for 10-15 minutes to complete the preparation.